Bianchi type-VI0 conformally invariant scalar fields - Ram S. (My University, 2025)
An exact solution of Einstein's equations corresponding to the conformally invariant scalar field with tracefree energy-momentum tensor as source is obtained in Bianchi type VI0 class of metrics. The solution represents a spatially homogeneous but anisotropy universe which admits anisotropic expansions. Some properties of the cosmological model are discussed. © 1984 D. Reidel Publishing Company.